A Smallholder Fish Trading Information System - Lim, Li Min; Nureize Arbaiy (Applied Information Technology And Computer Science, 2022)
The fish sales business is an important supply chain industry because it supplies the main food source to the people. Currently, information about sales transactions is managed by writing it in a ledger. When transaction data is handwritten on the record book, incorrect writing will inevitably occur. Therefore, a web-based system to handle the purchase transaction process, catch volume, and display each fish price per kilogram is proposed. Dedicated databases are also included to manage business data storage. The system provides a facility to record the catch which is an inventory of business stocks, dealer lists, sales records, and business analysis to allocate fish stocks to match the needs of traders. The system is used specifically by supplier, while buyers use the system to receive notifications from supplier if the fish harvest on that day meets their requirements, make invoices sent to supplier and check fish prices. Prototype models are used to facilitate project implementation. The programming language includes have PHP, HTML, CSS, while the MAMP and MySQL as the server and database. The process of this system is based on e-commerce methods and information systems. The need for e-commerce in this technological age is apparent, as it allows businesses to operate without regard to location or time limits. Eventually, this combination of e-commerce and web-based information systems can boost corporate efficiency and profitability at the same time.